Structural changes in Cz-Si single crystals irradiated with high-energy electrons from data of high-resolution X-ray diffractometry - Fodchuk, І.М.; Dovganyuk, V.V.; Litvinchuk, Т.V.; Kladko, V.P.; Slobodian, М.V.; Gudymenko, O.Yo.; Swiatek, Z. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Structural changes in silicon single crystals irradiated with high-energy electrons (Е = 18 MeV) were studied. The peculiarities of diffraction reflection curve behaviour and changes in the profiles of isodiffusion lines in high-resolution reciprocal space maps (HR-RSMs) were found as a function of the radiation dose. The generalized dynamic theory of X-ray Bragg-diffraction in crystals comprising defects of several types (spherical and disc-shaped clusters as well as dislocation loops) and a damaged nearsurface layer was used for explanation.